Stability and local environment of iron in vapor phase grown MgO nanocrystals - Niedermaier, Matthias; Dolcet, Paolo; Gheisi, Amirreza; Tippelt, Gerold; Lottermoser, Werner; Gross, Silvia; Bernardi, Johannes; Diwald, Oliver (Journal of Physical Chemistry C, 2017)
Metallocene injection into a metal combustion flame has been used for trapping transition metal ions inside MgO nanocrystals. Vacuum annealing changes the properties of resulting nonequilibrium solids toward thermodynamic equilibrium and provides means to control impurity localization and, as a result, the nanomaterials’ functional properties. By combining structure characterization (X-ray diffraction and transmission electron microscopy) with X-ray absorption spectroscopy and Mössbauer measurements, we tracked valence state and local chemical environment changes of Fe3+ ions inside vapor phase synthesized MgO nanocrystals. At a concentration of (1.5 ± 0.2) at. % Fe about (1400 ± 200) Fe3+ ions are effectively diluted within 12 nm sized nanocubes, where they form complexes between Fe3+ ions and Mg2+ vacancies. Increase of the iron concentration produces additional effects: enhanced ion diffusion and particle coarsening at elevated temperatures, clustering of Fe3+–Mg2+ vacancy complexes and, after annealing to T = 1173 K, the nucleation of a magnesioferrite phase that can be detected by X-ray diffraction for 4 at. % samples. At 3 at. % Fe, corresponding impurity ions induce surface energy changes that have a substantial impact on particle shape. With regard to the functional properties associated with transition metal ions in insulating MgO host lattices, the here presented insights underline that annealing-induced reorganization of oxide nanoparticles provides important parameters to control distribution and localization of impurity ion